Marcos conceptuales para un currículo crítico: una propuesta desde la pedagogía crítica brasileña, española y estadounidense - Toruño Arguedas, César (Universidad de Costa Rica, 2020)
This essay is based on the theoretical need to establish conceptual and operational frameworks to elaborate curricular proposals from a critical approach. This is achieved through a analysis of the main theorists of Brazilian, Spanish and American critical pedagogy, among which are Henry Giroux, Michael Apple, Ernest House, Paulo Freire, José Gimeno, Ángel Pérez, Miguel Santos, Jurjo Torres and Lawrence Stenhouse. The various theoretical productions were determined from an analysis of texts from files that allowed establishing the categories of analysis and their respective processing. The essay acquires its justification in the meantime, there are few systematization proposals for the construction of curricular designs from a critical pedagogy. Therefore, as a relevant contribution to the theoretical discussion, the construction of the conceptual and operational frameworks in the Education-Educational Center categories, teacher-student roles, curricular contextualization (teaching, learning and evaluation) and knowledge. This allows us to conclude that critical pedagogy has defined conceptual and operational frameworks that can favor the development of critical curricular designs with an emphasis on curricular contextualization. For which, it is necessary to update these delimiters within the curriculum management and innovation in the different stages of the education system.